Pediatric respiratory distress: California out‐of‐hospital protocols and evidence‐based recommendations. Issue 5 (8th June 2020) - Cheng, Tabitha; Farah, Jennifer; Aldridge, Nicholas; Tamir, Sharon; Donofrio‐Odmann, J. Joelle
Abstract: Objectives: Prehospital protocols vary across local emergency medical service (EMS) agencies in California. We sought to develop evidence‐based recommendations for the out‐of‐hospital evaluation and treatment of pediatric respiratory distress, and we evaluated the protocols for pediatric respiratory distress used by the 33 California local EMS agencies. Methods: Evidence‐based recommendations were developed through an extensive literature review of the current evidence regarding out‐of‐hospital treatment of pediatric patients with respiratory distress. The authors compared the pediatric respiratory distress protocols of each of the 33 California local EMS agencies with the evidence‐based recommendations. Our focus was on the treatment of 3 main pediatric respiratory complaints by presentation: stridor (croup), wheezing < 24 months (bronchiolitis), and wheezing > 24 months (asthma). Results: Protocols across the 33 California local EMS agencies varied widely. Stridor (croup) had the highest protocol variability of the 3 presentations we evaluated, with no treatment having uniform use among all agencies. Only 3 (9.1%) of the local EMS agencies differentiated wheezing in children < 24 months of age, referencing this as possible bronchiolitis. All local EMS agencies included albuterol and epinephrine (intravenous/intramuscular) in their pediatric wheezing (asthma) treatment protocols. The least common treatments for wheezing (asthma) included nebulized epinephrine (3/33) and magnesium (2/33). No agencies included steroids in their treatment protocols (0/33). Conclusion: Protocols for pediatric respiratory distress vary widely across the state of California, especially among those for stridor (croup) and wheezing in < 24 months (bronchiolitis). The evidence‐based recommendations that we present for the prehospital treatment of these conditions may be useful for EMS medical directors tasked with creating and revising these protocols.